Islamic Law and the Neoijtihadist Phenomenon - Takim, Liyakatali (Religions, 2021)
Many contemporary scholars claim that erstwhile juristic determinations were intertwined with the socio-political realities in the eighth and ninth centuries, the classical period of Islamic law. They also maintain that although the Qur’an is a divinely revealed and immutable text, the applicability of its verses is contingent on the needs and conditions of the times. This paper argues that there is a need to move beyond the current form of ijtihad to an era of neoijtihadism in Twelver Shi‘ism. The present ijtihad, which was developed in the medieval ages, has failed to produce a coherent legal system that can effectively respond to the needs of contemporary Muslims. The paper will focus on the neoijtihadist phenomenon and will argue that the traditional text-centered ijtihad has to be replaced with a new form of ijtihad which utilizes different forms of exegetical and epistemological principles to formulate rulings that will serve the Muslim community better. Neoijtihadism, as I call it, will entail a re-evaluation of classical juristic formulations and, based on the application of new exegetical and interpretive principles, can engender a divergent form of jurisprudence that is based on different epistemological parameters and universal moral values. Neoijtihadism will also entail revamping traditional Islamic legal theory (usul al-fiqh), which has hampered rather than enhanced the formulations of newer laws.